Risk factors for Central Nervous System drug use among nursing students - Victórya Suéllen Maciel Abreu; Davi Oliveira Teles; Hillary Bastos Vasconcelos Rodrigues; José Mateus Pires; Paula Renata Amorim Lessa Soares; Priscila de Souza Aquino; Samila Gomes Ribeiro (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to verify sociodemographic, academic and health risk factors for Central Nervous System drug use among nursing students. Methods: a cross-sectional study with 199 public undergraduate students from Ceará, using Characterization Instrument, Antonovsky's Sense of Coherence Questionnaire, Beck Depression Inventory and Beck Anxiety Inventory. Fischer's exact test and Pearson's chi-square test were performed, verifying an association between variables. Prevalence ratio was used. Results: a total of 34 used such drugs, with predominance of use of anxiolytics, associated with age (p=0.026), dissatisfaction with the relationship between classmates (p=0.003), insomnia (p=0.009), chronic disease (p=0.001), depression (p=0.035), and severe anxiety (p=0.023). Conclusions: using Central Nervous System drugs among students was associated with sociodemographic, academic and health factors, evidencing the need for actions promoting undergraduate students' mental health.